The Impact of Synectics Learning Model Implementation with Mind Mapping Assignments on Reducing Misconceptions and Enhancing Students' Cognitive Learning Outcomes - Nurul Kami Sani; I Wayan Darmadi; Nurgan; Kamaluddin (Jurnal Penelitian Pendidikan IPA, 2025)
Innovative learning models are essential to enhance students' cognitive abilities and address misconceptions in physics learning. This study aims to provide an overview of the influence of implementing the Synectics learning model with mind mapping assignments on the quantity of misconceptions and the cognitive learning outcomes of senior high school students. The research employed a quasi-experimental method using a randomized control group pretest-posttest design. The study was conducted on 11th-grade students at a senior high school in Palu, Central Sulawesi, during the 2023/2024 academic year. A cluster random sampling technique was used to select the sample. Data collection was carried out using pretests and posttests to measure the improvement in cognitive learning outcomes, while posttests were used to assess misconceptions experienced by students during learning with the Synectics model with and without mind mapping assignments. Observation sheets were also used to monitor the implementation of the learning process. The results showed an improvement in cognitive abilities for the experimental class, with an average normalized gain (N-Gain) of 0.63 (high), compared to 0.50 (moderate) for the control class. Based on a significance test at the 0.05 level, the findings revealed that the Synectics learning model with mind mapping assignments significantly outperformed the Synectics model without such assignments. Additionally, descriptive analysis of the misconceptions indicated that the Synectics model with mind mapping assignments resulted in fewer misconceptions compared to the model without mind mapping assignments.